An Antioxidant Component of Indonesian Herbs in Face Mist and Gel Spray Preparation: A Narrative Review - Fitri Mutiaraning Tyas; Nuria Ludvi Azizi; Nia Yuniarsih (HM Publisher, 2022)
Antioxidants for facial skin care would be better formulated in a topical form because the active substances will interact longer with facial skin. Indonesia is known for its wealth of natural ingredients that are useful as antioxidants. Research related to natural ingredients has been widely carried out and has good content for the skin. The good antioxidant content in herbal plants is in the form of secondary metabolites, namely flavonoids, alkaloids, phenolic compounds, carotenoids, tannins, steroids, and triterpenoids. This literature review aims to describe traditional Indonesian natural ingredients that have the potential to contain antioxidants that can be made into face mist and spray gel preparations. In conclusion, plants that can be formulated as face mist preparations are purple cabbage, yam tubers, and saffron flowers. Meanwhile, the herbs that can be used for spray gel preparations are strawberry fruit, buas-buas leaf, sweet orange peel, and purslane plant.